PP99 DETERMINATION OF THE ANTIOXIDANT AND ANTIBACTERIAL ACTIVITY OF EXTRACTS FROM THE AERIAL PARTS OF Dianthera secunda (Lam.) Griseb - Donato Caro, Campo Arfelly; Benitez Benitez, Ricardo; Martin Franco, Jaime (Revista Productos Naturales, 2026)
Oxidative stress and multidrug-resistant bacterial infections pose a global challenge to public health [1]. This study evaluated the antioxidant and antibacterial properties of extracts from Dianthera secunda (Lam.) Griseb, a plant used in traditional medicine [2,3].
Keywords: Antioxidant; antibacterial activity; Dianthera secunda